Earth system science : a very short introduction - Lenton, Tim (Oxford Oxford University Press, 2016)
The concept of the Earth's atmosphere, biosphere, oceans, soil, and rocks operating as a closely interacting system has rapidly gained ground in science. This new field, involving geographers, geologists, biologists, oceanographers, and atmospheric physicists, is known as Earth system science. This introductory text considers how a world in which humans could evolve was created; how, as a species, we are now reshaping that world; and what a sustainable future for humanity within the Earth system might look like. Drawing on elements of geology, biology, chemistry, physics, and mathematics, it also asks whether Earth system science can help guide us onto a sustainable course before we alter the Earth system to the point where we destroy ourselves and our current civilisation.--
Keywords: Earth sciences; Geoökosystem; Erde